Literary canon and teaching French as a Foreign Language (FLE): Cultural knowledge of wine through language - González Aguilar, Inés (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper comes to show the presence and influence of the literary canon in the teaching of French as a Foreign Language (FLE), conditioning the literary works in Spanish textbooks for this purpose. To this end, we have followed a path that starts with a theoretical analysis of the literary canon and the inclusion of culture in FLE and then shows how it has been a determining factor in civilizational teaching. This is supported by a specific study of the literature on wine culture. The conclusion is that this example allows us to check how the literary canon and literature merge in the FLE classroom.